Controlled synthesis of silver nanoplates and nanoparticles by reducing silver nitrate with hydroxylamine hydrochloride - Cheng, Zhi-Peng; Chu, Xiao-Zhong; Wu, Xiao-Qing; Xu, Ji-Ming; Zhong, Hui; Yin, Jing-Zhou (Rare metals, 2017)
An easy and effective method of silver nanoplate synthesis technique was created by reducing silver nitrate （AgNO3） with hydroxylamine hydrochloride （NH2OH·HCl） at room temperature. Silver nanoplates of various shapes, including triangular, truncated triangular, hexagonal, and truncated hexagonal, exhibit an average width and thickness of approximately 1 μm and 50 nm, respectively. Silver nanoparticles were acquired by placing polyvinyl pyrrolidone （PVP） in the reaction solution. The produced silver nanoparticles are quasi-spherical in shape and - 100 nm in size. The catalytic activity in the thermal decomposition of ammonium perchlorate （AID） was distinguished by thermogravimetric （TG） analysis and differential scanning calorimetry （DSC）. The outcomes reveal that the addition of silver nanoplates and nanoparticles diminishes the low decomposition temperature of AP by 7 and 14 ℃ and leads to a drop in the high decomposition temperature of AP by 60 and 110 ℃ and a rise in the total DSC heat release by 0.86 and 1.05 kJ.g^-1, respectively.